The (im)possibility of monitoring and evaluating the impact of community engagement performance in South African universities: A review - Netshandama , V. O. (South African Journal of Higher Education, 2023)
Monitoring and evaluation (M&E) allow universities to learn from past experiences, improve service delivery, plan, and allocate resources and demonstrate results as part of their accountability to stakeholders. M&E also assists in keeping projects on track, providing a basis for reassessing priorities and creating evidence-based data for projects. Considerable scholarship is illuminating insights and sharing experiences of community engagement in higher education. However, the question of M&E remains contestable due to the complexities in implementing community engagement in higher education. This article discusses the (im)possibility of facilitating M&E in higher education community engagement spaces. In 2009, the University of Venda established a directorate for community engagement, which I became its first director. I use the insider lens to reflect on the intersections of concepts and constructs such as knowledge co-production, ecosystems, societal impact, and an M&E framework in higher education. I intend here to bring some problems and contestations in generating a framework for monitoring and reviewing community engagement, arguing that the framework should embrace multiple ontologies and be intentional about robust engagement with epistemological, ontological, and ethical questions around exclusivity and dominance. Hopefully I will add a much-needed dimension acknowledging the complexity of a community engagement discourse – toward an inclusive, participatory-ecosystemic way of self-assessment, monitoring and evaluation.